Concomitant Transatrial and Transapical CRT-D Lead Implantation in a Patient with Chest Burn Injury - Riba, Adam; Rashed, Aref; Toth, Roland; Tahin, Tamas (The Thoracic and Cardiovascular Surgeon Reports, 2022)
Cardiac resynchronization therapy device with defibrillator (CRT-D) implantation is indicated for patients with a history of malignant ventricular arrhythmias, symptomatic heart failure, wide QRS, or high-degree atrioventricular block. A 67-year-old patient with dilated cardiomyopathy received a CRT-D with the conventional method but 1 month later skin necrosis was diagnosed above the device. The complete system was extracted from the patient and we utilized negative pressure wound therapy for the treatment of the remaining tissue. We decided to perform surgical reimplantation of the device using minithoracotomy: right atrial and right ventricular leads were introduced through the right atrial appendage and the left ventricular lead was inserted transapically. The device was implanted under the less scabby abdominal skin. We successfully applied the combination of transatrial and transapical lead placement, which has not been reported in the literature yet. It serves as an alternative method if the standard approach is not feasible.
Keywords: heart failure; minimally invasive surgery (includes port access, minithoracotomy); wound healing